Occupational and Operational Risk Assessment in Trans Jogja Public Transportation Using HIRADC and FTA - Adhe Yuliawan; Rifano Rifano; Dwi Wahyu Hidayat; Mokhammad Rifqi Tsani (JTI: Jurnal Teknik Industri, 2026)
Urban public transportation operations are exposed to a range of operational, technical, and human-factor risks that may lead to traffic accidents, occupational injuries, and service disruptions. However, previous transportation safety studies have rarely integrated workshop hazards, operational routes, and driver-related risks within a unified risk-management framework. Therefore, this study aims to develop an integrated operational risk-control framework for urban public transportation systems using the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) and Fault Tree Analysis (FTA) methods. This study employed a mixed-method descriptive approach involving workshop activities, operational routes, and driver-related operational factors in Trans Jogja operations. Data were collected through observations, interviews, and questionnaires involving mechanics and drivers. The HIRADC analysis identified several high-risk activities related to workshop operations, traffic conditions, and driver performance, particularly welding activities, manual handling, congested intersections, aggressive road-user behavior, and driver fatigue. Furthermore, the FTA results revealed that accident risks were influenced by interactions among human, managerial, technical, and environmental factors. Recommended control measures include stricter implementation of standard operating procedures, defensive driving training, ergonomic improvements, optimization of driver work-rest schedules, and traffic engineering improvements. The findings demonstrate that safety risks in urban public transportation systems are multidimensional and interconnected across operational domains. This study contributes by integrating HIRADC-based risk assessment with FTA-based root cause analysis to support comprehensive transportation safety risk management. Keywords: HIRADC, FTA, Risk Control, Trans Jogja, Transportation Safety.